Synthesis and Characterization of Conducting Copolymers of (S)‐2‐Methylbutyl‐2‐(3‐thienyl)acetate with Pyrrole and Thiophene - Levent, A.; Toppare, Levent Kamil; Cianga, I.; Yagci, Y. (Wiley, 2003)
AbstractPolymerization of methylbutyl‐2‐(3‐thienyl)acetate (MBTA) was achieved by constant current electrolysis at low temperature. Subsequently, the syntheses of block copolymers of polyMBTA were accomplished in the presence of either pyrrole or thiophene by constant potential electrolysis. Moreover, the copolymer of MBTA with thiophene was obtained with constant potential electrolysis.The synthesis of monomer MBTA.magnified imageThe synthesis of monomer MBTA.
Keywords: Polymers and Plastics; Organic Chemistry; Materials Chemistry; Physical and Theoretical Chemistry; Condensed Matter Physics